Persepsi Musisi Folk Surabaya Berlabel Independen Terhadap Media Baru Sebagai Sarana Komunikasi - Adhi Pradana, Bagus Cahyo Shah (representamen, 2019)
ABSTRACTIn the music industry, record labels are divided into two. The first is the independent record label better known as the indie label, and the second is the major record label known as the major label. Major labels are known as a huge record labels in the music industry, while indie labels are associated with smaller industries. Indie labels, the distribution tends to be uneven and not in official distribution stores or through communities. Indie musicians do more publications through new media, especially social media. Few of the independent musicians is Yuvi and Briliyan, who are personnel from the band Humi Dumi. Social media is used, among others, Instagram and Twitter, facebook, spotify, Youtube, and soundcloud. Therefore, this study aimed to analyze perception of the folk musicians in independent label about new media as a communication medium. This study is a qualitative study using the case study method. This type of research is descriptive research that is supported by the data collection technique through observation, interview, and documentation. The result of this study demonstrate the use of new media that include Instagram, Twitter, Soundcloud, Spotify, Youtube, and website as a medium to communicate. With new media, the interaction between Briliyan and Yuvi and fans becomes easier. With a good interaction, the awareness of the audience to independent musician will also increase.Keywords: Perception, New Media, Independent Music, Communication